2018
DOI: 10.1007/s10120-018-0838-6
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal metastasis as a predictive factor for nab-paclitaxel in patients with pretreated advanced gastric cancer: an exploratory analysis of the phase III ABSOLUTE trial

Abstract: Background In the ABSOLUTE trial, weekly nanoparticle albumin-bound paclitaxel (w-nab-PTX) showed non-inferiority to weekly solvent-based paclitaxel (w-sb-PTX) for overall survival (OS). Thus, w-nab-PTX might be an option for secondline chemotherapy in advanced gastric cancer (AGC). However, predictive factors for efficacies of these agents have not been evaluated. Methods Patients previously enrolled in the ABSOLUTE trial were divided into apparent peritoneal metastasis group (PM group) and no apparent perito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 17 publications
5
34
0
1
Order By: Relevance
“…This theory is consistent with taxan-containing therapies showing superior results than other regimens for treating gastric cancer [37,38]. Half of the patients with unresectable GC have PM at the time of second-line chemotherapy induction [2,38]. Because ICI was used after treatment failure of taxan-containing therapies, the phenotype of macrophages may have changed from M1 to M2 in the PM TME.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…This theory is consistent with taxan-containing therapies showing superior results than other regimens for treating gastric cancer [37,38]. Half of the patients with unresectable GC have PM at the time of second-line chemotherapy induction [2,38]. Because ICI was used after treatment failure of taxan-containing therapies, the phenotype of macrophages may have changed from M1 to M2 in the PM TME.…”
Section: Discussionsupporting
confidence: 55%
“…Low-dose paclitaxel changed macrophage phenotype from M2 to M1 through the toll-like receptor (TLR)-4, resulting in tumor growth inhibition [35,36]. This theory is consistent with taxan-containing therapies showing superior results than other regimens for treating gastric cancer [37,38]. Half of the patients with unresectable GC have PM at the time of second-line chemotherapy induction [2,38].…”
Section: Discussionmentioning
confidence: 64%
“…In a subgroup analysis, PFS in patients with moderate/massive ascites tended to be better with nab-PTX plus RAM than PTX plus RAM. The ABSOLUTE trial, which demonstrated the non-inferiority of weekly nab-PTX to weekly PTX for patients with AGC, also suggested an increased efficacy of weekly nab-PTX in patients with ascites or peritoneal metastasis [11,16]. While the reason for this remains unclear, a multicenter randomized phase II P-SELECT trial of nab-PTX plus RAM versus PTX plus RAM as second-line therapy for AGC patients with peritoneal dissemination (WJOG10617G, jRCTs031180022) is underway and may confirm this observation.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned previously, GCYA patients are likely to have good bone marrow function and could tolerate this intensive regimen. Furthermore, in a subgroup analysis of the ABSOLUTE trial, 32 it has been reported that nab-paclitaxel has greater efficacy for peritoneal metastasis than paclitaxel. Most GCYA patients had diffuse-type histology.…”
Section: Discussionmentioning
confidence: 99%